Prognostic value of systemic immune-inflammation index (SII) in cancers: a systematic review and meta-analysis - Tang, Jian-Ning; Goyal, Hemant; Yu, Sisi; Luo, Huaichao (Journal of Laboratory and Precision Medicine, 2018)
Background: Systemic immune-inflammation index (SII) is calculated by the value which is based on peripheral lymphocyte, neutrophil, and platelet counts, has been recently investigated as a valuable prognostic marker in several types of tumors. However, the combined prognostic value of SII for these tumors remains unclear. Here, we quantify the prognostic impact of this index and assess its consistency in a motley of cancers. Methods: We conducted a systematic review of PubMed/Medline, Cochrane Library, American Society of Clinical Oncology (ASCO), and European Society for Medical Oncology (ESMO) with a final date of April 20, 2017. Data from relevant studies reporting a hazard ratio (HR) and 95% confidence interval (CI) were pooled in a meta-analysis. The meta-analysis was conducted by using RevMan 5.3 and STATA software. Results: Thirteen studies comprising 4,104 patients were included in the final analysis. The median cutoff for SII was 575. The aggregate results indicated that elevated SII was associated with poor overall survival (OS) (HR =1.80; 95% CI: 1.43–2.28), poor cancer-specific survival (CSS) (HR =1.44; 95% CI: 1.04–1.99), time to recurrence (TTR) (HR =1.91; 95% CI: 1.53–2.43) and poor progression-free survival (PFS) (HR =1.18; 95% CI: 0.55–2.52). Further analysis found similar results in various subgroups stratified by cancer type, sample size, and ethnicity. Conclusions: Our meta-analysis shows that SII may be a potentially useful prognostic biomarker in patients with cancer. We suggest the need for further investigations to delineate the utility of SII for clinical decision making in this population.